2010
DOI: 10.1017/s0022112009994101
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent rotating convection at high Rayleigh and Taylor numbers

Abstract: We report heat transport measurements in a cylindrical convection apparatus rotating about the vertical axis. The aspect ratio was 1/2. The working fluid was cryogenic helium gas and the following parameter ranges applied: the Rayleigh number, Ra, varied in the range 1011 < Ra < 4.3 × 1015, the Taylor number, Ta, varied in the range 1011 < Ta < 3 × 1015, the convective Rossby number, Ro, varied in the range 0.4 < Ro < 1.6 and the Prandtl number, Pr, varied in the range 0.7 < Pr < 5.9. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 24 publications
(34 reference statements)
5
36
0
Order By: Relevance
“…This force acts in the circumferential direction only and may qualitatively alter the flow from a condition of a domain filling large-scale circulation (at low constant rotation rates) or dispersed local thermal plumes (at high constant rotation rates), to a more or less segregated situation in which a pronounced thermal column forms along the centreline of the domain and highly sheared structures appear in the boundary layer near the vertical sidewalls. Situations displaying this thermal column were found to support a strongly increased Nusselt number, indicating a striking qualitative similarity with findings from the experimental work reported in Niemela et al (2010). The experimental work was conducted at different flow conditions, e.g., a higher Rayleigh number and a different Prandtl number, which are currently not accessible for DNS.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This force acts in the circumferential direction only and may qualitatively alter the flow from a condition of a domain filling large-scale circulation (at low constant rotation rates) or dispersed local thermal plumes (at high constant rotation rates), to a more or less segregated situation in which a pronounced thermal column forms along the centreline of the domain and highly sheared structures appear in the boundary layer near the vertical sidewalls. Situations displaying this thermal column were found to support a strongly increased Nusselt number, indicating a striking qualitative similarity with findings from the experimental work reported in Niemela et al (2010). The experimental work was conducted at different flow conditions, e.g., a higher Rayleigh number and a different Prandtl number, which are currently not accessible for DNS.…”
Section: Discussionsupporting
confidence: 77%
“…Such an increase in the Nusselt number at appropriate Rossby numbers is due to Ekman pumping, which is efficient only for r > 1 and is gradually reduced once the Rayleigh number is increased . Hence the study by Niemela et al (2010) has revealed a reduction of Nu under rotation: in liquid helium at r ¼ 0:7 and at very high Ra $ Oð10 11 À 10 15 Þ there is no effective Ekman pumping, while the damping of vertical motion by rotation is already felt.…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of recent interest in these studies have been transitions between rotationally dominated and nonrotating turbulent states (2-10) and the enhancement of heat transport by rotation (6,8,(11)(12)(13)(14)(15). Numerical simulations of planetary dynamo action by rotating convection also concentrate on fluids with unit order Pr (16).…”
mentioning
confidence: 99%
“…In comparison to numerous studies of RC in moderate Prandtl number fluids [11,13,14,20,23,[63][64][65][66][67][68][69][70], only a rather limited number of rotating convection investigations have been made in low Prandtl number fluids [18][19][20]51,71]. The governing equations for rotating convection are i.e., the angular velocity Ω = 0.84 rad/s and the rotation period P Ω = 7.5 s. The height of the layer is fixed at H = 10 cm.…”
Section: Essential Theorymentioning
confidence: 99%